Contemporary adolescent literature and culture : the emergent adult - Hilton, Mary, 1946-; Nikolajeva, Maria (Ashgate studies in childhood, 1700 to the present., 2012)
Offering a wide range of critical perspectives, this volume explores the moral, ideological and literary landscapes in fiction and other cultural productions aimed at young adults. Topics examined are adolescence and the natural world, nationhood and identity, the mapping of sexual awakening onto postcolonial awareness, hybridity and trans-racial romance, transgressive sexuality, the sexually abused adolescent body, music as a code for identity formation, representations of adolescent emotion, and what neuroscience research tells us about young adult readers, writers, and young artists. Throughout, the volume explores the ways writers configure their adolescent protagonists as awkward, alienated, rebellious and unhappy, so that the figure of the young adult becomes a symbol of wider political and societal concerns. Examining in depth significant contemporary novels, including those by Julia Alvarez, Stephenie Meyer, Tamora Pierce, Malorie Blackman and Meg Rosoff, among others, Contemporary Adolescent Literature and Culture illuminates the ways in which the cultural constructions 'adolescent' and 'young adult fiction' share some of society's most painful anxieties and contradictions.